ANALISIS KETIMPANGAN PEMBANGUNAN DAN DISTRIBUSI PENDAPATAN WILAYAH DI PROVINSI ACEH - Muhammad Reza; Abd. Jamal; T. Zulham (Syiah Kuala University, 2019)
Abstract The aims of this research are to understand the development disparities, income distribution, human development, and the geographical difficulties in North-East, Center-South East, and West-South of Aceh Regions. The methods of analysis used are Williamson Index, Lorentz Curve, Gini Coefficient, Human Development Index (IPM), and Geographical Difficulties Index (IKG). The results show that based on Williamson Index, the developments in the North-East, Center-South East Regions of Aceh are still low. Based on the Lorenz Curve, West-South Region is far from equality line, it is followed by Center-South East and North-East Regions. Thus, it can be stated that West-South and Center-South East Regions experience relatively greater income disparities compared to North-East Region. Based on Human Development Index Calculation, West-South of Aceh is the region that has lowest Human Development Index, then it followed by Center-South East and North-East Regions of Aceh. Based on Geographical Difficulties Index, West-South Region of Aceh has the highest Geographical Difficulties Index compared to Center-South East and North-East Regions of Aceh viewed from the existence of basic services, infrastructure condition, and transportation.The government must strive to reduce development disparities in the North-East, Central-Southeast and West-South regions of Aceh so that there will be no provincial division and conflict between regions.